ISLAMIC LEGAL PERSPECTIVE ON CONTENTIOUS MARRIAGE ISBAT IN GIRI MENANG RELIGIOUS COURT - Muhasim, Ahmad; Abdullah, Abdullah; Nuruddin, Nuruddin (Universitas Islam Negeri Mataram, 2025)
Contentious marriage confirmation is a solution given to people whose husband/wife has died and whose marriage has not been registered at the Office of Religious Affairs. This study examines two important things, namely, how contentious marriage confirmation is applied at the Giri Menang Religious Court, West Lombok, and how Islamic law reviews the application. The method used in this study is qualitative, field research type, with a normative legal approach. The results of this study indicate that the application for contentious marriage confirmation at the Giri Menang Religious Court is for (1) Completeness of personal identity to take care of making the applicant's child's birth certificate; (2) Disbursement of the Applicant's Husband's Death Insurance Fund; (3) Completeness of Personal Identity and Transfer of the Deceased Hajj Pilgrim's Seat Number; (4) Completeness of Personal Identity and Management of BPJS Employment Funds. In making a decision/determination on the application for contentious marriage confirmation, the Panel of Judges at the Giri Menang Religious Court considers the following: (1) Consideration that the marriage is valid according to religion; (2) Consideration that the marriage can be proven and meets the material and formal elements and requirements of proof such as written evidence and witnesses; (3) Consideration that the marriage confirmation is made for administrative purposes; and (4) Consideration of public interest. The marriage confirmation of contentiousness in Islamic law can be accepted as long as there is sharia evidence that supports the existence of a valid marriage contract. Although the formal form of marriage confirmation is not known in classical fiqh, its substance is very much in line with the values ​​of Islamic law. Therefore, the institution of marriage confirmation of contentiousness in Indonesian religious courts is an application of sharia principles in the context of modern state and society.